HETERODINUCLEAR GROUP-6 METALLACARBORANES - SYNTHESIS AND CHARACTERIZATION OF [CLOSO-3,3,3-(CO)3-3-SNPH3-3,1,2-MC2B9H11]-(M = CR, MO, W) - KIM, JW; DO, YK; SOHN, YS; KNOBLER, CB; HAWTHORNE, MF (ELSEVIER SCIENCE SA LAUSANNE, 1991)
Heterodinuclear group 6 metallacarborane anions [closo-3,3,3-(CO)3-3-SnPh3-3,1,2-MC2B9H11]-(M = Cr, 2; Mo, 3; W, 4) were prepared from the equimolar reaction systems of Tl2C2B9H11/M(CO)3(MeCN)3/SnPh3Cl/(PPN)Cl in MeCN as the [PPN]+ (PPN+ = bis(triphenylphophoranylidene ammonium cation) salts and were characterized by various means including multinuclear NMR and single-crystal X-ray diffraction. Crystals of [PPN].4 are monoclinic, C2/c, with a = 45.777(4), b = 11.669(1), c = 26.826(3) angstrom, beta = 125.134(2)degrees, V = 11718 angstrom 3 and Z = 8. Convergence was achieved with R (R(w)) = 6.7 (8.0)% for 5487 (I > 3-sigma(I)) observed reflections. The nido anion C2B9H11(2-) interacts with W via the C2B3 pentagonal] plane and forms the closo WC2B9 geometry. The W-Sn distance of 2.825(1) angstrom and the observation of 1J(Sn-119-W-183) = 262 Hz in Sn-119 NMR spectrum of 4 establish the presence of a W-Sn bonding interaction. The structural integrities of 2, 3 and 4 are similar and each compound remains intact in solution.